Mabuiag Community Booklet 2012. - Torres Strait Regional Authority ([Thursday Island, Queensland] : [Torres Strait Regional Authority], 2012)
The Torres Strait and Northern Peninsula Regional Plan 2009-2029 was developed to address the need for a whole-of-region plan to guide the development of the Torres Strait and Northern Peninsula Area into the future. This Community Booklet aims to explain the range of government services available in the Hammond community and the region, and who is responsible for those services, and to monitor the progress of delivering the additional services identified for the community in the Torres Strait and Northern Peninsula Regional Plan 2009-2029.
Early childhood -- Schooling -- Health -- Economic participation -- Healthy homes -- Safe communities -- Governance and leadership.
Title from PDF cover page (viewed on April 16, 2014)
At head of PDF cover page: Torres Strait and Northern Peninsula area regional plan 2009-2029.
At head of PDF cover page: Closing the gap.
Mode of access: Available online (as at 16/04/14) at: http://www.tsra.gov.au/media-and-publications/publications/regional-plan-community-booklets-2012.
Keywords: Regional planning -- Queensland -- Mabuiag Island; Social planning -- Queensland -- Mabuiag Island; Economic development -- Queensland -- Mabuiag Island; Community development -- Queensland -- Mabuiag Island; Human services -- Queensland -- Mabuiag Island; Mabuiag / Jervis Island (Qld TSI SC54-07); Torres Strait Islands (Qld.) -- Economic conditions; Torres Strait Islands (Qld.) -- Social conditions